2017
DOI: 10.1021/acs.est.7b00698
|View full text |Cite
|
Sign up to set email alerts
|

Resource Footprints are Good Proxies of Environmental Damage

Abstract: Environmental footprints are increasingly used to quantify and compare environmental impacts of for example products, technologies, households, or nations. This has resulted in a multitude of footprint indicators, ranging from relatively simple measures of resource use (water, energy, materials) to integrated measures of eventual damage (for example, extinction of species). Yet, the possible redundancies among these different footprints have not yet been quantified. This paper analyzes the relationships betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(46 citation statements)
references
References 49 publications
1
44
0
1
Order By: Relevance
“…; Steinmann et al. , ). If such a limited set was found sufficient for emerging technologies, it would be convenient in order to reduce data requirement.…”
Section: Recommendations and Future Workmentioning
confidence: 97%
“…; Steinmann et al. , ). If such a limited set was found sufficient for emerging technologies, it would be convenient in order to reduce data requirement.…”
Section: Recommendations and Future Workmentioning
confidence: 97%
“…If we consider all categories that could be included in LCA regarding ES, the impact assessment of LCA would easily consist of at least 27 midpoint impact categories in total. While some efforts have focused on trying to find common ground among existent categories to minimize the amount of impact categories needed in the impact assessment of LCA (Steinmann et al, 2017), it is also arguable that the impact assessment of LCA is still considerably limited, and the addition of impact categories assessing a wide range of impacts is essential to improve its robustness. A major complication is that this increased number of impact categories complicates the interpretation and decision making based on LCA results.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, Sabia et al [34] observed that for 1 kg of sheep milk using the ReCiPe endpoint approach, the impacts in terms of damage on biodiversity was equal to 3.29 E-07 species*year. Steinmann et al [72] observed that this damage can be the result of the combination of land and energy footprints. In addition, [73] observed that agronomic practices may undermine both soil and water quality while also negatively affecting the natural biodiversity through, for example, N deposition in ecosystems.…”
Section: Effect On Biodiversity With Two Different Methodsmentioning
confidence: 99%